The power of diversity in the Armed Forces : international perspectives on immigrant participation in the military - Scoppio, Grazia; Greco, Sara (Human dimensions in foreign policy, military studies, and security studies, 2022)
"While countries throughout the world rely on immigrants to support their populations and economies, access to the military remains limited or denied to those who have not yet acquired citizenship. Precluding immigrants from serving in their host country's armed forces is an issue of moral equity and operational effectiveness. Allowing immigrants to enlist ensures that the military represents the population it serves and encourages inclusivity and cultural change within the institution, while also creating a more effective military force. The Power of Diversity in the Armed Forces investigates how different countries approach the inclusion or exclusion of immigrants in their armed forces and offers immigrant military participation as a way to provide a pathway to citizenship, foster greater societal integration, and achieve a more equitable, diverse, and inclusive military. By surveying international perspectives on immigrant/non-citizen military participation in twelve countries, The Power of Diversity in the Armed Forces introduces and examines a new way to unlock the power of diversity in military organizations globally."--